PENYULUHANSPIRITUAL EMOTIONAL FREEDOM TECHNIQUE(SEFT) SEBAGAI SOLUSI KESEHATAN PADA WARGADUSUN BABADAN,SELOMIRAH, NGABLAK,MAGELANG,JAWA TENGAH - Mellisa Fitri Ardtiyani (UII, 2014)
Spiritual emotional freedom technique (SEFT) is one technique of alternativemedicine that have been old enough known. This technique is a development of othertechniques introduced by the nation's children. SEFT including relaxation techniques, isone form of alternative medicine that is easier and safer than acupuncture andacupressure. Because it is easier and cheaper then the dissemination of this technique iseasier to do, one of them on the people of Dusun Babadan. Babadan dusun who haveobtained the information about this method can be used as an alternative medicine andfitness in their homes.